Preparation method and application of magnesium nitrate / carbide slag / fly ash composite adsorbent with high cycle stability
Through the preparation method of magnesium nitrate/calcium carbide slag/fly ash composite adsorbent, the multi-frame structure and optimized process conditions are used to solve the problem of reduced CO2 performance in cyclic capture of calcium carbide slag, and high cycle stability and low cost CO2 are achieved Capture effect.
Patent Information
- Application Number
- CN202411711828.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-01-07
AI Technical Summary
The existing calcium carbide slag cyclic capture CO2 performance decreases with the increase of cycle times, resulting in the need to increase the amount of addition and increase the operating cost and threaten the safety of the equipment. The existing modified calcium-based adsorbent methods are complex and costly.
The preparation method of magnesium nitrate/calcium carbide slag/fly ash composite adsorbent is prepared by raw material pretreatment, mixing, heating and combustion synthesis methods, optimize particle size, mass ratio and calcining conditions, and form a multi-frame structure to improve cycle stability .
The performance of calcium carbide slag cyclic capture of CO2 was significantly improved. The adsorption performance decayed after 20 cycles was only 0.04g·g-1, maintaining a 90.5% cycle stability, reducing production costs.
Smart Images

Figure CN119258978A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon dioxide capture materials, in particular to a preparation method and application of a magnesium nitrate / carbide slag / fly ash composite adsorbent with high cycle stability. Background Art
[0002] At present, carbide slag is used as a high-temperature absorbent in the calcium cycle method to cyclically capture CO2 in the tail flue gas of coal-fired boilers, realizing a process route that combines resource utilization of carbide slag with CO2 removal. Experimental results show that carbide slag exhibits good CO2 capture performance. However, with the increase in the number of cycles, the performance of carbide slag in cyclic capture of CO2 decreases rapidly. Experiments show that after 20 cycles, the carbonation conversion rate of carbide slag drops significantly. In order to maintain a high CO2 capture efficiency, it is necessary to increase the amount of carbide slag added to the reactor, which not only increases the operating cost, but also causes increased wear of the reactor, threatening the safe operation of the equipment. Therefore, it is of great significance to study how to improve the CO2 capture performance during the carbide slag cyclic reaction and slow down the attenuation of the carbide slag cyclic carbonation conversion rate as the number of cycles increases.
[0003] At present, most researchers improve the cyclic stability of adsorbents by modifying calcium-based materials by adding rare earth elements, transition metals, alkali metal salts or using composite materials. Some researchers also improve the pore structure of adsorbents by different preparation methods, such as spray drying, sol-gel method, combustion synthesis method and hydrothermal method, etc. However, these methods are relatively complex and costly, and their effects on improving adsorbent performance vary. Therefore, it is of great significance to study low-cost, efficient and clean methods of modifying calcium-based materials. Summary of the invention
[0004] In view of the shortcomings of the prior art, the technical problem to be solved by the present invention is how to improve the cycle stability of carbide slag while reducing production costs, so as to improve the performance of carbide slag in cyclic capture of CO2. To this end, the present invention provides a preparation method and application of a magnesium nitrate / carbide slag / fly ash composite adsorbent with high cycle stability.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a magnesium nitrate / carbide slag / fly ash composite adsorbent with high cyclic stability, comprising the following steps:
[0007] (1) Pretreatment of raw materials: grind, sieve and dry calcium carbide slag, fly ash and magnesium nitrate hexahydrate respectively for later use;
[0008] (2) mixing carbide slag with deionized water, stirring, first adding fly ash, then adding magnesium nitrate hexahydrate and citric acid, stirring evenly, heating in a constant temperature water bath until viscous, then drying, grinding, and setting aside;
[0009] (3) The product is calcined by combustion synthesis method in air atmosphere, and then cooled to room temperature by nitrogen.
[0010] Among them, carbide slag is mixed with deionized water to further increase the content of calcium hydroxide in the carbide slag while ensuring sufficient mixing; the addition of citric acid provides a carbon template for the combustion synthesis method, further enriches the pores of the adsorbent, and improves the cyclic stability of the adsorbent.
[0011] Preferably, in step (1), after screening, the particle size of carbide slag is ≤74 μm, the particle size of fly ash is ≤74 μm, and the particle size of magnesium nitrate hexahydrate is ≤74 μm;
[0012] The present invention selects carbide slag, fly ash and magnesium nitrate hexahydrate with a particle size of ≤74 μm, and fully dopes the raw materials under the condition of small and consistent particle sizes to improve the cycle stability of the composite adsorbent.
[0013] Preferably, in step (1), the drying temperature is 120° C. and the drying time is 12 h;
[0014] Preferably, in step (2), the mass ratio of carbide slag, fly ash and magnesium nitrate hexahydrate is (9.5-7): (0.5-3): (14-16);
[0015] More preferably, in step (2), the mass ratio of carbide slag, fly ash and magnesium nitrate hexahydrate is 9:1:15;
[0016] Among them, the present invention mixes carbide slag, fly ash and magnesium nitrate hexahydrate in a suitable doping ratio. If too little fly ash and magnesium nitrate are doped, sufficient skeleton support and porosity improvement cannot be achieved, and the maximum improvement of performance cannot be achieved. Excessive doping of fly ash and magnesium nitrate will reduce the total CO2 adsorption of the adsorbent under the same mass. Therefore, after reasonable regulation, the present invention selects this doping ratio, and the best cycle stability of the adsorbent can be achieved after the three are mixed.
[0017] Preferably, in step (2), the volume ratio of carbide slag to deionized water is 1 g:5 mL;
[0018] Preferably, in step (2), the mass ratio of carbide slag to citric acid is 1:3;
[0019] Preferably, in step (2), the citric acid is anhydrous citric acid;
[0020] Preferably, in step (2), the water bath heating temperature is 80° C. and the time is 3 h;
[0021] Preferably, in step (2), the drying temperature is 120° C. and the drying time is 12 h; the particle size of the mixture after grinding is ≤74 μm;
[0022] Among them, the present invention heats the mixed raw materials to a viscous state under the constant temperature water bath conditions and performs a drying process. The water bath heating is used to maximize the removal of moisture in the raw materials, ensure that different precursors inside the adsorbent are fully mixed and evenly mixed, and provide a uniform escape space for the gas escape prepared by subsequent calcination.
[0023] Preferably, in step (3), the calcination temperature is 750-950°C and the time is 0.5-2h;
[0024] More preferably, in step (3), the calcination temperature is 850° C. and the calcination time is 1 h.
[0025] Among them, when the calcination temperature and time are too low, the crystallinity of calcium oxide is low, and the pore collapse and sintering phenomena are more serious during the cycle; when the calcination temperature is too high, the fly ash will react with part of the calcium, occupy the adsorption sites of the adsorbent and thus reduce the adsorption performance.
[0026] In addition, the present invention adopts the combustion synthesis method for calcination treatment. While the carbide slag becomes a calcium-based substrate, the fly ash evolves into the main inert skeleton, and magnesium nitrate acts as a derivative skeleton while emitting a large amount of NO2 gas. Not only the cyclic stability of the adsorbent is improved by the coexistence of multiple skeletons, but also a rich pore structure is constructed to improve the CO2 adsorption performance of the adsorbent.
[0027] The invention provides an application of a magnesium nitrate / carbide slag / fly ash composite adsorbent with high cycle stability. The magnesium nitrate / carbide slag / fly ash composite adsorbent is prepared by using the preparation method; the application is the constant temperature adsorption of carbon dioxide.
[0028] Preferably, the isothermal adsorption temperature of carbon dioxide is 650-750°C.
[0029] More preferably, the isothermal adsorption temperature of carbon dioxide is 750°C.
[0030] The technical solution of the present invention achieves the following beneficial technical effects:
[0031] The invention is based on the principle of coexistence of multiple frameworks, and fly ash and magnesium nitrate hexahydrate are used to dope carbide slag, wherein the fly ash is the main inert framework, the magnesium nitrate is the derived framework, and the carbide slag is the calcium-based substrate. The invention also optimizes the raw material particle size, the mass ratio of the three mixed, the calcination temperature and time and other process conditions to regulate the change of the adsorbent microstructure and the derivation of the inert framework, so as to support the adsorbent pores without occupying the calcium-based adsorption sites, and slow down the pore collapse caused by sintering. The invention also wet mixes, adds citric acid, heats in a constant temperature water bath, and then dries and grinds, and then uses a combustion synthesis method to prepare a magnesium nitrate / carbide slag / fly ash composite adsorbent, so as to further enrich the adsorbent pores while fixing the adsorbent microstructure, so that the adsorbent has an adsorption performance attenuated by only 0.04 g·g after 20 cycles of adsorption. -1 After 20 cycles, the adsorption capacity can still reach 0.38 g·g -1 , the cyclic stability of the adsorbent is greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 Thermogravimetric analysis of carbide slag and fly ash in Example 1 of the present invention;
[0033] Figure 2 The temperature swing adsorption curve of the adsorbent in Example 3 of the present invention;
[0034] Figure 3 The temperature-variable desorption curve of the adsorbent in Example 3 of the present invention;
[0035] Figure 4 Constant temperature adsorption curve diagram of the adsorbent at different temperatures in Example 3 of the present invention;
[0036] Figure 5 Cyclic adsorption and desorption curve diagram of the adsorbent in Example 4 of the present invention;
[0037] Figure 6 Cyclic adsorption and desorption curve diagram of the adsorbent in Example 5 of the present invention;
[0038] Figure 7 Cyclic adsorption and desorption curve diagram of the adsorbent in Example 6 of the present invention;
[0039] Figure 8 Cyclic adsorption and desorption curve diagram of the adsorbent in Example 7 of the present invention;
[0040] Fig. 9 SEM image of the adsorbent before cyclic adsorption in Example 2 of the present invention;
[0041] Among them, (a) 955CFA 74 -82; (b)91CFA 74 -82; (c)82CFA 74 -82; (d)73CFA74 -82(e)91CFA 250 -82; (f) 91CFA 74 -81; (g)91CFA 74 -8 0.5 ; (h)91CFA 74 -71; (i) 91CFA 74 -91;
[0042] Fig.10 SEM image of the adsorbent after 20 cycles of adsorption in Example 2 of the present invention;
[0043] Among them, (a) 955CFA 74 -82; (b)91CFA 74 -82; (c)82CFA 74 -82; (d)73CFA 74 -82(e)91CFA 250 -82; (f) 91CFA 74 -81; (g)91CFA 74 -8 0.5 ; (h)91CFA 74 -71; (i) 91CFA 74 -91;
[0044] Fig.11 Cyclic adsorption and desorption curve diagram of the adsorbent in Example 8 of the present invention;
[0045] Fig.12 SEM images of the adsorbent in Example 8 of the present invention before and after 20 cycles of adsorption;
[0046] Among them, (a) 73CX-81 before cycling; (b) 73CX-81 after cycling;
[0047] (c) 91CFA before cycle 74 -73CX-81; (d) 91CFA after cycling 74 -73CX-81. DETAILED DESCRIPTION
[0048] The raw materials used in the following embodiments of the present invention are:
[0049] Carbide slag: Grind the carbide slag evenly in an agate mortar, and then sieve to obtain carbide slag with a particle size of less than 200 mesh (i.e., 74 μm), named Car; finally dry it in a blast drying oven at 120°C, let it stand for 12 hours, and then set aside;
[0050] Fly ash: Fly ash was ground evenly in an agate mortar and then sieved to obtain fly ash with particle sizes less than 200 mesh, 200 mesh to 60 mesh (i.e., 250 μm), and named as FA, 74 , FA 250 Finally, dry it in a 120°C forced air drying oven, let it stand for 12 hours, and set aside.
[0051] Magnesium nitrate hexahydrate: Grind magnesium nitrate hexahydrate evenly in an agate mortar, and then sieve to obtain magnesium nitrate hexahydrate with a particle size of less than 200 mesh (i.e., 74 μm), named CX; finally dry in a blast drying oven at 120° C., let stand for 12 hours, and set aside.
[0052] Example 1 Determination of calcination temperature
[0053] Carbide slag (Car) and fly ash (FA 74 ) were mixed in a mass ratio of 6:4 and named 64CFA; then poured into a sealed container and vibrated for 20 minutes, and then placed in a TG thermogravimeter. The temperature was raised from room temperature to 1000°C at 10°C / min under N2 atmosphere for thermal decomposition experiment; and the same thermal decomposition experiment was performed on carbide slag (Car) alone. The results are shown in the figure. Figure 1 shown.
[0054] Depend on Figure 1 It can be seen that 64CFA and Car are completely thermally decomposed at about 700°C, and fly ash blending does not decompose during the thermal decomposition process. Based on this, the calcination temperature range for preparing fly ash / carbide slag adsorbent is determined to be 700°C-1000°C. The present invention further studies the effects of different temperatures of 750°C, 850°C, and 950°C on the preparation of adsorbent.
[0055] Example 2 Preparation of carbide slag / fly ash adsorbent
[0056] Carbide slag (Car) and fly ash (FA 74 , FA 250 ) were mixed in different mass ratios (70:30, 80:20, 90:10, 95:5); after grinding, they were calcined at 750℃, 850℃, and 950℃ in air atmosphere for 0.5h, 1h, and 2h, respectively, and then N2 was introduced to cool to room temperature to obtain adsorbent samples (the raw material ratios and preparation conditions of each adsorbent are shown in Table 1). Different samples were placed in sealed bags and N2 was introduced for standby use.
[0057] Table 1 Preparation conditions of adsorbent
[0058] Calcination temperature Calcination time Fly ash particle size (μm) Carbide slag / fly ash mass ratio name 850℃ 2h 74-250 90:10 <![CDATA[91CFA 250 -82]]> 850℃ 2h 0-74 95:5 <![CDATA[955CFA 74 -82]]> 850℃ 2h 0-74 90:10 <![CDATA[91CFA 74 -82]]> 850℃ 2h 0-74 80:20 <![CDATA[82CFA 74 -82]]> 850℃ 2h 0-74 70:30 <![CDATA[73CFA 74 -82]]> 850℃ 0.5h 0-74 90:10 <![CDATA[91CFA 74 -8 0.5 ]]> 850℃ 1h 0-74 90:10 <![CDATA[91CFA 74 -81]]> 750℃ 1h 0-74 90:10 <![CDATA[91CFA 74 -71]]> 950℃ 1h 0-74 90:10 <![CDATA[91CFA 74 -91]]>
[0059] In the table, 91CFA 74-82 as an example: 91 means the mass ratio of carbide slag to fly ash is 90:10; CFA 74 It indicates that the particle size of fly ash is 0-74μm; 82 indicates that the calcination temperature is 850℃ and the time is 2h.
[0060] Example 3 Determination of adsorption and desorption temperature of adsorbent
[0061] Select 91CFA prepared in Example 2 74 -82 adsorbent, the adsorption and desorption temperature of fly ash / carbide slag adsorbent was analyzed. The adsorbent was subjected to temperature-variable adsorption and desorption experiments in a pure CO2 atmosphere on a TG thermogravimeter, and the TG curve was differentiated to obtain the differential thermogravimetric (DTG) curve. The results are as follows Figure 2 , 3 shown.
[0062] according to Figure 3 The desorption rate of the adsorbent reaches the maximum at 858℃ and is completely desorbed at 880℃, so 880℃ is selected as the desorption temperature of the adsorbent. Figure 2 The adsorbent adsorbs CO2 at 550℃-800℃, and the adsorption rate reaches the maximum at 680℃. Therefore, 650℃, 700℃, and 750℃ were selected for constant temperature adsorption TG experiments to analyze and determine the optimal adsorption temperature of the adsorbent. The results are shown in Figure 4 .
[0063] from Figure 4 It can be seen that as the adsorption temperature increases, the adsorption amount of the adsorbent changes from a rapid increase to a slow increase, and the adsorption capacity corresponding to 750°C maintains a leading position throughout the adsorption stage, so 750°C is selected as the adsorption temperature of the adsorbent.
[0064] Cyclic performance test: Weigh 0.5 g of the adsorbent sample to be tested (Table 1) and conduct a cyclic adsorption-desorption experiment in a tube furnace. First, heat it to 880 °C and pre-calcine it in a N2 atmosphere for 15 min. Then, cool it down to 750 °C in a N2 atmosphere, introduce CO2 for adsorption for 30 min, and then introduce N2 and heat it to 880 °C for calcination for 15 min. Repeat the adsorption-desorption experiment for 20 cycles. The weight change (g g -1 ) as the ordinate and the number of cycles (N) as the abscissa to plot the cyclic adsorption-desorption curve. The cyclic stable adsorption performance of the adsorbent is evaluated by the weight change of the adsorbent after the cycle (i.e., the mass of CO2 adsorbable per 1g of adsorbent / g).
[0065] Adsorbent weight change (g g -1 ) = (weight of adsorbent after this cycle of adsorption / g - weight of adsorbent before this cycle of adsorption / g) / weight of adsorbent before this cycle of adsorption (g)
[0066] Example 4 Determination of fly ash particle size
[0067] Select 91CFA prepared in Example 2 250 -82,91CFA 74 -82 adsorbent was used for the experiment, and carbide slag (Car) and calcium oxide (CaCO3) were used as comparisons. The cycle performance determination experimental method in Example 3 was referred to, and the adsorbent performance was analyzed by the cycle adsorption and desorption curve. The results are as follows Figure 5 shown.
[0068] from Figure 5 It can be seen that the adsorption capacity of carbide slag adsorbent was not effectively improved after mixing with fly ash, but the cycle stability was greatly improved. After 10 cycles, the adsorption of carbide slag and CaCO3 tended to be flat, and the adsorption change of the composite adsorbent was 0.1g·g higher than the other two. -1 The fly ash mixed with carbide slag with a particle size of 0-74 μm has higher cycle stability, and the adsorption capacity (i.e., adsorbent weight change) remains at 0.267 g g after 20 cycles. -1 .
[0069] Example 5 Determination of Carbide Slag / Fly Ash Mass Ratio
[0070] Select 955CFA prepared in Example 2 74 -82,91CFA 74 -82, 82CFA 74 -82,73CFA 74 -82 adsorbent was used for the experiment, and the cyclic performance determination experimental method in Example 3 was referred to, and the adsorbent performance was analyzed by cyclic adsorption and desorption curves. The results are as follows: Figure 6 shown.
[0071] from Figure 6 It can be seen that the cyclic stability of fly ash / carbide slag adsorbents with different mass ratios increases first and then decreases with the increase of fly ash blending ratio (95:5, 9:1, 8:2, 7:3), among which 91CFA 74 -82 has the best cycle stability, and its adsorption capacity remains at 0.267 g·g after 20 cycles. -1 .
[0072] Example 6 Determination of Calcination Time
[0073] Select 91CFA prepared in Example 2 74 -8 0.5 、91CFA 74 -81,91CFA 74 -82 adsorbent was used for the experiment, and the cyclic performance determination experimental method in Example 3 was referred to, and the adsorbent performance was analyzed by cyclic adsorption and desorption curves. The results are as follows: Figure 7 shown.
[0074] from Figure 7 It can be seen that the adsorption capacity and cycle stability of fly ash / carbide slag adsorbent change with the calcination time. With the increase of calcination time, the adsorption capacity and cycle stability show a trend of first increasing and then decreasing. 74 -81 The first adsorption capacity can reach 0.519 g·g -1 After 20 cycles, the adsorption capacity remained at 0.31 g·g -1 .
[0075] Example 7 Determination of Calcination Temperature
[0076] Select 91CFA prepared in Example 2 74 -71, 91CFA 74 -81,91CFA 74 -91 adsorbent was used for the experiment, and the cyclic performance determination experimental method in Example 3 was referred to, and the adsorbent performance was analyzed by cyclic adsorption and desorption curves. The results are as follows: Figure 8 shown.
[0077] from Figure 8 It can be seen that when the calcination temperature is low, the first adsorption capacity reaches a maximum of 0.519 g·g at 750 °C and 850 °C. -1 At a high temperature of 950°C, the first adsorption capacity dropped significantly to 0.42 g·g -1 ; For cycle stability, the thermal conductivity of the samples at higher temperatures of 850°C and 950°C was still 0.31 g·g after 20 cycles. -1 , 0.319 g·g -1 The adsorption capacity is high and the cycle stability is high.
[0078] Furthermore, the SEM images of the 9 adsorbents prepared in Example 2 and the adsorbents after 20 cycles of adsorption were analyzed. Figure 9-10 shown.
[0079] Depend on Figure 9-10 It can be seen that compared with other adsorbents, the prepared 91CFA 74 -81 composite adsorbent has rich pore structure and obvious skeleton, while other adsorbents have alternating macropores and micropores; and after cyclic adsorption, 91CFA 74 The surface of the -81 composite adsorbent is sintered to a certain extent, but there are still a large number of small pores inside that can be used for CO2 adsorption.
[0080] Combined with Examples 4-7, it can be seen that the optimal preparation process conditions of fly ash / carbide slag composite adsorbent are: 0-74μm fly ash particle size, 0-74μm carbide slag particle size, carbide slag / fly ash mass ratio of 9:1, calcination temperature of 850℃, and calcination time of 1h.
[0081] Example 8 Preparation of magnesium nitrate / carbide slag / fly ash composite adsorbent
[0082] Based on the above experiments, fly ash only improves the cyclic stability of carbide slag adsorbent. In order to further improve the adsorption capacity of carbide slag adsorbent, the synergistic effect of fly ash / magnesium nitrate on carbide slag adsorbent was explored. Since carbide slag and fly ash are both water-insoluble mixtures, mechanical mixing was used to study the preparation conditions of the two. Magnesium nitrate hexahydrate is a water-soluble substance that does not react with carbide slag and fly ash. In order to achieve full mixing of magnesium nitrate hexahydrate and enhance the modification effect of magnesium nitrate hexahydrate, the synergistic effect of fly ash / magnesium nitrate on carbide slag adsorbent was explored. On the basis of the above, magnesium nitrate hexahydrate was added by wet mixing for analysis, and citric acid was added to enhance the gas dissipation effect of magnesium nitrate hexahydrate itself during the preparation of the adsorbent. Under the preparation conditions of calcination temperature of 850°C and calcination time of 1h, fly ash will not react with carbide slag, and it still maintains the state of mullite, only supporting the adsorbent as an inert component. Therefore, magnesium nitrate hexahydrate was added under the optimal preparation conditions of fly ash / carbide slag composite adsorbent to prepare magnesium nitrate / carbide slag / fly ash composite adsorbent:
[0083] In order to dissolve citric acid and mix different precursors more evenly, 10 mL of deionized water was added to 2 g of carbide slag. After stirring, 0.222 g of fly ash was added first, followed by 3.33 g of magnesium nitrate hexahydrate and 6 g of anhydrous citric acid, and the mixture was stirred evenly. The mixture was placed in a constant temperature water bath at 80 ° C for 3 h, and it was viscous at this time. The mixture was then placed in a drying oven at 120 ° C for 12 h. After grinding, the mixture was calcined at 850 ° C for 1 h in an air atmosphere (oxygen was provided and the mixture was prepared by combustion synthesis method), and N2 was introduced to cool the mixture to room temperature to obtain an adsorbent sample named 91CFA. 74 -73CX-81.
[0084] Preparation of magnesium nitrate / carbide slag composite adsorbent: add 10 mL of deionized water to 2 g of carbide slag, stir, then add 3.33 g of magnesium nitrate hexahydrate and 6 g of anhydrous citric acid, stir evenly; place in a constant temperature water bath at 80°C for 3 hours, then place in a drying oven at 120°C for 12 hours; after grinding, calcine at 850°C for 1 hour in an air atmosphere, pass N2 and cool to room temperature to obtain an adsorbent sample, named 73CX-81.
[0085] The carbide slag / fly ash composite adsorbent 91CFA prepared in Example 2 was selected 74 -81, and 91CFA prepared in this example 74-73CX-81, 73CX-81 were tested, and the cycle performance test method in Example 3 was referred to, and the adsorbent performance was analyzed by the cycle adsorption and desorption curve. The results are as follows: Fig.11 shown.
[0086] Depend on Fig.11 It can be seen that when magnesium nitrate and fly ash are co-doped, fly ash mainly supports the pore structure of the adsorbent, and magnesium nitrate enriches the pore structure. The two synergistically improve the cyclic stability of the adsorbent, and the adsorption attenuation of the adsorbent after 20 cycles is only 0.04 g·g -1 After 20 cycles, the adsorption capacity can still reach 0.38 g·g -1 , the cycle stability reaches 90.5%;
[0087] And 91CFA 74 -81 composite adsorbent adsorbs 0.209 g·g after 20 cycles -1 After 20 cycles, the adsorption capacity was 0.31 g·g -1 The cycle stability is 59.7%; the adsorption decay of 73CX-81 adsorbent after 20 cycles is 0.1 g g -1 After 20 cycles, the adsorption capacity was 0.35 g·g -1 , the cycle stability is 77.8%. 74 -73CX-81 The cycle stability of the adsorbent is greatly improved. The present invention utilizes wet mixing and combustion synthesis methods, and through reasonable adjustment of the doping ratio of the three raw materials of fly ash, magnesium nitrate hexahydrate, and carbide slag in the preparation process, as well as process parameters such as temperature and time, a composite adsorbent with a cycle stability of more than 90% is obtained. If the preparation method described in the present invention is not adopted, it is impossible to achieve the cycle stability of the adsorbent described in the present invention.
[0088] Further, 73CX-81 and 91CFA prepared in this example 74 -73CX-81 adsorbent, and the SEM images of the adsorbent after 20 cycles of adsorption were analyzed. The results are as follows Fig.12 shown.
[0089] Depend on Fig.12 It can be seen that the prepared 91CFA 74 -73CX-81 composite adsorbent has dense internal pores, while 73CX-81 adsorbent shows particle accumulation; and after cyclic adsorption, 91CFA 74 -73CX-81 composite adsorbent has less sintering phenomenon. 74-73CX-81 composite adsorbent is based on the principle of multi-frame coexistence, with fly ash as the main inert frame, magnesium nitrate as the derivative frame, and carbide slag as the calcium-based base. By regulating the changes in the adsorbent microstructure and the derivation of the inert frame, the adsorbent pores are supported without occupying the calcium-based adsorption sites, slowing down the pore collapse caused by sintering, making 91CFA 74 -The cyclic stable adsorption capacity of the 73CX-81 composite adsorbent is improved.
[0090] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the claims of this patent application.
Claims
1. A method for preparing a magnesium nitrate / carbide slag / fly ash composite adsorbent with high cyclic stability, characterized in that: The following steps are involved: (1) Pretreatment of raw materials: grind, sieve and dry calcium carbide slag, fly ash and magnesium nitrate hexahydrate respectively for later use; (2) mixing carbide slag with deionized water, stirring, first adding fly ash, then adding magnesium nitrate hexahydrate and citric acid, stirring evenly, heating in a constant temperature water bath, then drying, grinding, and setting aside; (3) The product is calcined by combustion synthesis method in air atmosphere, and then cooled to room temperature by nitrogen.
2. The preparation method according to claim 1, characterized in that In step (1), after screening, the particle size of carbide slag is ≤74 μm, the particle size of fly ash is ≤74 μm, and the particle size of magnesium nitrate hexahydrate is ≤74 μm; the drying temperature is 120° C., and the drying time is 12 hours.
3. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of carbide slag to deionized water is 1 g:5 mL; the mass ratio of carbide slag to citric acid is 1:
3.
4. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of carbide slag, fly ash and magnesium nitrate hexahydrate is (9.5-7): (0.5-3): (14-16).
5. The preparation method according to claim 4, characterized in that: In step (2), the mass ratio of carbide slag, fly ash and magnesium nitrate hexahydrate is 9:1:
15.
6. The preparation method according to claim 1, characterized in that: In step (2), the water bath heating temperature is 80° C. for 3 h; the drying temperature is 120° C. for 12 h.
7. The preparation method according to claim 1, characterized in that: In step (3), the calcination temperature is 750-950° C. and the calcination time is 0.5-2 h.
8. The preparation method according to claim 7, characterized in that: In step (3), the calcination temperature is 850° C. and the calcination time is 1 h.
9. Application of a magnesium nitrate / carbide slag / fly ash composite adsorbent with high cyclic stability, characterized in that: The magnesium nitrate / carbide slag / fly ash composite adsorbent is prepared using the preparation method described in any one of claims 1 to 8; the application is to use the magnesium nitrate / carbide slag / fly ash composite adsorbent for isothermal adsorption of carbon dioxide.
10. The use according to claim 9, characterized in that The isothermal adsorption temperature of carbon dioxide is 650-750℃.